Silence of the guns. The history of the Long Toms of the Anglo-Boer War, Louis Changuion : book review (Historia, 2021)
This, surely, must be one of the most enjoyable books published during the commemoration of the Anglo-Boer War. And it is yet another book from the admirable Nicol Stassen’s Protea Book House. Changuion has been cherishing this topic for a long time and people fortunate enough to have heard his fascinating lectures on the issue will certainly not be disappointed by the final product. It is indeed a very readable book, combining two other essential elements for a successful product, viz. thorough research and meticulous field work. There have been earlier attempts to record the fascinating history of the four Boer 155 mm Creusot garrison guns, the most notable being the publications of Darell Hall (Long Tom and The Hall handbook of the Anglo Boer War 1899-1902). But with Changuion’s book we have the expert researcher and writer on the job, and a man who knows how to tell a good story.
Keywords: commemoration; Anglo-Boer War